AN ECONOMIC ANALYSIS OF THE IMPACT OF TRADE OPENNESS ON AGRICULTURAL OUTPUT GROWTH IN IRAQ FOR THE PERIOD 1990-2020 - Bashar, A. S.; Al-Wasity, R. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research aimed to measure the impact of trade openness and changes in the terms of trade on the growth of agricultural domestic product in Iraq for the period 1990-2020. The independent variables were represented by indicators (trade openness, agricultural exports, the rate of trade of agricultural crops, and the exchange rate). The Autoregressive Distributed Lag Model (ARDL) measures the relationship between variables, in addition to the PP test for the stability of the time series. After the estimated model passed the bounds test, the short-run and long-run functions were estimated. The results of the estimation in the short run showed the existence of a positive effect of both terms of trade and the exchange rate on the growth of agricultural domestic product. As for the rate of trade openness, its effect was negative, and the results did not prove significant for the agricultural export index. In the long term, it was significant. As for trade openness, its effect became positive due to the growth of exports in the long term. The results indicated that the terms of trade are not in the country’s favor, due to the small volume of agricultural exports.